2011
DOI: 10.2478/v10059-011-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept and self-esteem: How the content of the self-concept reveals sources and functions of self-esteem

Abstract: Self-concept and self-esteem: How the content of the self-concept reveals sources and functions of self-esteem The relations of content of self-concept to self-esteem may reflect the role of different factors in developing self-esteem. On the basis of theories describing sources of self-esteem, we distinguished four domains of self-beliefs: agency, morality, strength and energy to act, and acceptance by others, which we hypothesized to be related to self-esteem. In two studies, involving 411 university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
20
0
2
Order By: Relevance
“…Through various interpersonal relationships and multiple social comparisons, people learn who they are and gradually develop positive or negative views of themselves. Positive self-expansion (e.g., increasing one’s status, economic position, or affiliation; Beck and Haigh, 2014 ) and perception of competence and acceptance from others ( Lachowicz-Tabaczek and śniecińska, 2011 ) are suggested to be associated with increased self-esteem. In contrast, perceived chronic social adversity could lead to negative beliefs about the self.…”
Section: Symptomatic Sequelae Of Perceived Chronic Social Adversitymentioning
confidence: 99%
“…Through various interpersonal relationships and multiple social comparisons, people learn who they are and gradually develop positive or negative views of themselves. Positive self-expansion (e.g., increasing one’s status, economic position, or affiliation; Beck and Haigh, 2014 ) and perception of competence and acceptance from others ( Lachowicz-Tabaczek and śniecińska, 2011 ) are suggested to be associated with increased self-esteem. In contrast, perceived chronic social adversity could lead to negative beliefs about the self.…”
Section: Symptomatic Sequelae Of Perceived Chronic Social Adversitymentioning
confidence: 99%
“…According to theoretical work, social support is important in determining self-esteem [26]. Perception of acceptance from others is demonstrated to be associated with increased self-esteem [27]. A considerable amount of empirical research found that one's level of self-esteem may significantly be predicted by PSS [28,29].…”
Section: The Mediating Effect Of Self-esteemmentioning
confidence: 99%
“…Cultural standards may include not only personal achievements but also moral principles, basic order, and harmony within the in-group. An individual achieves high selfesteem and a feeling of immortality when he or she fulfils cultural demands [6]. This includes the individual's perception of his nature and abilities, interactions with others and the environment, values related to experience and objects, his goals and desires.…”
Section: B Self-conceptmentioning
confidence: 99%